Scar endometriosis: a rare complication of cesarean section - Goel, Sugandha; Goel, Bina; Tiwari, Aakanksha; Modh, Maitri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Scar endometriosis, also known as incisional endometriosis, is a rare condition characterized by the presence of functional endometrial tissue in surgical scars, most commonly after cesarean sections or gynecological procedures. We report a case of 34-year-old woman (P2L2) presented with a pain and swelling in the previous LSCS abdominal scar since 1year. Imaging revealed a hypoechoic lesion suggestive of endometriosis. Surgical excision was performed, and histopathology confirmed the diagnosis. Postoperative follow-up indicated complete symptom resolution and no recurrence on follow up. Wide local surgical excision is the definitive treatment for permanent cure.